Determinants of mortality in children aged under two years in Bangladesh using two approaches: an analysis of the Bangladesh Demographic and Health Survey 2014 data - Rahman, Md Sazedur; Rahman, Md Ashfikur; Afroze, Laila; Rahman, Md Saidur; Khan, Abdul Gaffar; Mahmud, Zarzis Al; Shariful Islam, Sheikh Mohammed (Bangladesh Journal of Medical Science, 2022)
Aims: Mortality in children aged under two years is a severe public health problem in many developing countries. The aims of the study were to reveal the prevalence and factors associated with mortality in children under two years in Bangladesh. Methods: Data were analyzed using the Bangladesh Demographic and Health Survey 2014. A total of 7886 participant data used in this study. The chi-square test of association was performed with dependent and independent variables to measure the prevalence rate, while the final model binary logistic and log-binomial regressions were used to identify the potential risk factors for under-two mortalities. Results: The prevalence of under-2 mortalities in Bangladesh was 3.9%. Regression analysis revealed that a lower level of paternal education, succeeding birth interval less than 24 months, multiple birth babies, and smaller than the average size at birth were significantly associated with children’s mortality under two years in Bangladesh. Conclusions: Despite improvements in the reduction of child mortality in Bangladesh, many children died within the first 24 months of life, mostly preventable. Programs towards increasing education levels and pregnancy intervals might help in preventing infant mortality in Bangladesh. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 413-421